A murine model for cerebral toxocariasis: characterisation of host susceptibility and behaviour. - HOLLAND, CELIA; STAFFORD, PETER (My University, 2006)
Toxocara canis, the parasitic roundworm of dogs, can infect a number of paratenic hosts, such as mice and humans, due to the widespread dissemination of its ova in the environment. In these paratenic hosts, larvae have been shown to exhibit a predilection for the central nervous system, resulting in an increasing number of parasites migrating to the brain as infection progresses. In an initial experiment, we investigated the differential brain involvement of T. canis in 7 strains of inbred mice, and chose 2 strains, susceptible (BALB/c) and resistant (NIH) to cerebral infection. In a second experiment, both strains were investigated in terms of course of migration, larval accumulation, and behavioural response to T. canis infection. Results revealed that infected BALB/c mice took significantly longer to drink from a water source (following a period of deprivation), compared with control mice, indicating some degree of memory impairment. Cerebral larval recoveries from both strains of mice demonstrated variation between the two experiments, suggesting that larval burdens may not be a reliable indicator of susceptibility or resistance to T. canis infection. The percentage of total recovered larvae in each organ may be a better representation of larval distribution. Our model system may provide insights into the impact of chronic geohelminth infection on cognitive development.
PUBLISHED
Keywords: Zoology; Toxocara canis